Power User's Guide to Windows Development - Darby, Jason
Microsoft Windows is the most popular operating system in the world. Millions of computers are shipped every year with it as the OS, making Windows the platform of choice for developers. And because of its widespread use, there are numerous programming languages that can be used to create applications that will work with Windows. But you don't have to be a programmer to develop practical, fun, and interesting applications with Windows. Many people have learned how to harness the power of Windows to make their own tools and the Power User's Guide to Windows Development will teach you how to create your own without knowing how to program! Written for power Windows users, Web developers, and beginning programmers who want to go beyond the basic functional uses of Windows, but who aren't programmers, this book is a complete guide to making your own games, music players, CD-ROM menus, screensavers, movie players, advertising materials, and more. Using a free trial version of Multimedia Fusion 2 Developer (Clickteam), youÂ'll learn how to develop your own tools within Windows. A variety of fun projects are used throughout the book to get you developing practical applications quickly. Beginning with basic screen savers, you'll progress through edutainment tools, interactive tutorials, games, CD-ROM menus, graphic creation, videos, music, and networking tools. So, if you want to make your own applications to use on Windows, the Power User's Guide to Windows Development will teach you everything you need to know-- no programming required!